Phenotypic Stability of Agave Species on Bouldery Wastelands (Riverbed) of Doon Valley - Gupta, R. K.; Agarwal, M. E.; Joshie, P. (Indian Forester, 1997)
Study on seven species of Agave (viz., amaniensis, angustifolia, cantala, elongata, hybrid, miradoransis and sisalana) was carried out to identify the most stable Agave species under bouldery riverbed wastelands of Doon Valley. The analysis of the data indicated that the amount of variability existed not only among species but also in the environments. All these species differed considerably in respect to their stability for different characters under study. Three Agave species (viz., A.angustifolia, A.hybrid and A.miradoransis) did not show stable performance at all, while two species of Agave (viz., A.amaniensis and A.cantala) has shown stable performance for one character only. Agave elongata showed stable performance for four growth characters, while Agave sisalana has shown stable performance for three growth characters and also for the fibre yield. Agave sisalana was found to be the only stable Agave species and hence could be recommended for mass adoption on bouldery wastelands of Doon Valley.